Recent research into healthcare professions regulation: a rapid evidence assessment - Julie Browne; Alison Bullock; Chiara Poletti; Dorottya Cserző (BMC, 2021)
Abstract Background and aims Over the last decade, regulators have taken significant steps towards tackling perceptions that regulatory systems are burdensome. There has been much international research activity in the regulation of health and care professionals. This article reports a review of studies on health professions regulation between January 2011 and March 2020. Its chief object was to provide robust and up-to-date evidence to assist regulators in policy development and implementation. The main objectives of this study were to: 1. Identify and retrieve research in the field of health and care professions regulation in English since 2011; 2. Evaluate the published research, exploring its utility to regulators and practitioners, and drawing out any key messages; 3. Draw conclusions concerning the scope and limitations of the research literature and identify areas for further research. Methods We undertook a rapid evidence assessment (REA) of the international literature on health and care professions regulation, including reviewing ten UK regulators' websites to identify issues of concern and strategic priorities. We retrieved 3833 references, using a four-stage screening process to select the 81 most relevant. Results Results are reported within six key themes: harm prevention and patient safety; fitness to practise; quality assurance of education and training; registration including maintenance of registers; guidelines and standards and relations with regulatory bodies. Conclusions Regulation of professionals in health and care is comparatively undeveloped as a field of academic study. Consequently, the published evidence is diffuse and small-scale. Most work presents relatively weak data of low relevance to regulators, mainly reporting or describing the current position. Few studies are able to show the impact of regulation or demonstrate a causal link between regulation and its effects. To inform their research and policy agendas health and social care regulators need to commission, interpret and apply the scholarly literature more effectively; academics need to engage with regulators to ensure that their research provides high-quality evidence with practical relevance to the regulators' agendas. Further study is needed to explore how effective academic collaborations between regulators and researchers may be created and sustained.